PENGARUH KETIDAK PASTIAN LINGKUNGAN BISNIS TERHADAP KINERJA ORGANISASI - TOTAL QUALITY MANAGEMENT SEBAGAI PEMODERASI - Yerlin Birana; Ferdinandus Sampe (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this research is to describe and analyze the relationship between employee empowerment and service quality improvement. The approach used is a quantitative descriptive approach. The research population is culinary companies in the city of Makassar. Data were collected using a survey with the technique of determining the company as the sample is the convenience sampling technique. A total of 120 questionnaires were circulated to be filled out by the owner, manager or at least the supervisor level. A total of 97 questionnaires were returned and after being checked, were declared complete for analysis. Data analysis was carried out descriptively and then tested for validity and reliability. Valid and reliable indicators of employee empowerment and service quality are then tested with classical assumptions to ensure that the data found can be processed parametrically, namely correlation and regression analysis for hypothesis testing. The results of the correlation analysis show that there is a strong correlation between employee empowerment and service quality improvement and the results of the hypothesis test state that employee empowerment has a significant effect on improving service quality. The implication of this research is that continuous empowerment of employees needs to be done so that the quality of service is getting better. It is recommended that further research be carried out in other business.